Carbon Storage Potential of Talang Forest in Pinggir District, Bengkalis Regency, Riau Province - Pebriandi; Defri Yoza; Wishnu Sukmantoro; Evi Sribudiani; Viny Volcherina Darlis; Sonia Somadona; Nur Suhada; Niskan Walid Masruri; Ahmad Baiquni Rangkuti (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2023)
The Indonesian government is committed to reducing carbon and greenhouse gas emissions through the Forestry and Other Land Uses (FOLU) Net-Sink 2030 scheme. Efforts that can be made to support the FOLU Net-Sink 2030 is by knowing the carbon storage potential in a forest area. This research aims to calculate the amount of potential biomass carbon storage in the talang forest. The methods used in this research are non-destructive sampling and destructive sampling. The method with destructive sampling for seedlings, understorey and litters, while for saplings, poles, trees and necromass with non-destructive sampling method. The calculation results showed that carbon stocks were trees (77.76 tons/ha), poles (9.56 tons/ha), saplings (7.99 tons/ha), seedlings and understorey (0.65 tons/ha), litters (1.20 tons/ha) and necromass (2.39 tons/ha). Aboveground carbon storage in the talang forest was found to be 99.56 tons/ha. The total aboveground carbon storage potential of the gutter forest was 7,933 tons of carbon.